The Influence of Capability Managerial on Competitiveness of the Company through the Planning Strategy, Investment, Innovation and Performance of the Company (a Study on Corporate Manufacturing Industry Group B Medium Sized Territory Gerbang Kertosusila, - Soelaksono, Tedjo; Sudiro, Achmad; Rahayu, Mintarti; Sudjatno, Sudjatno (International Review of Management and Marketing, 2018)
Purpose of this study was to analyze the influence of managerial capabilities to the company’s competitiveness through strategic planning, investment, innovation and the company’s performance in the manufacturing industry in the mid-scale class B Gerbang Kertosusila Territory, East Java. The research sample number of 125 companies manufacturing industry in the middle of class B scale Gerbang Kertosusila Territory, East Java. Sampling by using purposive sampling (manufacturing industry group B) with cluster sampling (based on Gerbang Kerosusila area), as for the calculation of cluster sampling by using proportional random sampling. Research questionnaire used as an instrument of primary data collection. Data analysis technique used is the analysis of Structural Equation Modeling.The variables used in this study, including the ability of the managerial, strategic planning, investment, innovation, the company’s performance and competitiveness. The results showed the managerial capacity affect the company’s competitiveness through strategic planning, innovation, investment, and corporate performance. Keywords: managerial capabilities, strategic planning, investment, innovation, the company’s performance, competitiveness. JEL Classifications: D8, L2